PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA DENGAN MOTIVASI SEBAGAI VARIABEL MODERATING - Irianti, Maria Theresia Femi; Utami, Setyaningsih Sri (Universitas Slamet Riyadi, 2012)
ABSTRACT This study aims to analyze the significance of the effect of: (1) variables of leadership style on job satisfaction, (2) the work environment variables on job satisfaction, (3) motivation variables on job satisfaction, (4) variable moderating effect of motivation on the effect of leadership style on job satisfaction , (5) variable moderating effect of motivation on the effect of work environment on job satisfaction. Its population is 70 employees Mother and Child Hospital Award Semarang. Samples were taken 70 people by census method. The data collection technique using a questionnaire with validity and reliability. Engineering analysis using multiple linear regression with the classic assumption test. Conclusion of the study: (1) a significant effect of leadership style on job satisfaction verified, (2) The working environment has no significant effect on job satisfaction, (3) Motivation significant effect on job satisfaction, (4) Motivation does not moderate the effect of leadership style on satisfaction employment, (5) Motivation moderating influence of work environment on job satisfaction. Keywords: leadership style, work environment, motivation, job satisfaction.